A City in Blue and Green The Singapore Story - Rowe, Peter G. (Springer Nature, 2019)
This open access book highlights Singapore's development into a city in which water and greenery, along with associated environmental, technical, social and political aspects have been harnessed and cultivated into a liveable sustainable way of life. It is also a story about a unique and thoroughgoing approach to large-scale and potentially transferable water sustainability, within largely urbanized circumstances, which can be achieved, along with complementary roles of environmental conservation, ecology, public open-space management and the greening of buildings, together with infrastructural improvements.